Dictyophora-derived N-doped porous carbon microspheres for high-performance supercapacitors. (1st September 2020) - Zuo, Saisai; Gao, Jingping; Wu, Fuming; Yang, Bingye; Sun, Yu; Xie, Minhui; Mi, Xue; Wang, Wei; Liu, Yu; Yan, Jing
Abstract : PCMS- T hierarchical porous structures were prepared from biomass dictyophora as electrodes for high-performance supercapacitors. Abstract : In this paper, natural dictyophora has been used as a precursor to synthesize nitrogen-doped porous carbon microspheres (PCMS) by hydrothermal carbonization and subsequent KOH activation at different temperatures (650–850 °C). This unique structure of PCMS is conducive to the penetration and mobility of ions. The PCMS were characterized using different analysis technologies and their capacitive performance was investigated. The results indicate that the PCMS activated at 750 °C (PCMS-750) exhibited the highest specific capacitance, 380 F g −1, at the current density of 1 A g −1 . The excellent electrochemical performance can be attributed to the structure of novel porous microspheres and effective N self-doping. The symmetric supercapacitor device based on the PCMS-750 electrodes exhibited high energy density (27.50 W h kg −1 at a power density of 899.9 W kg −1 ) and excellent cycle stability (94.1% after 10 000 cycles). Such a high-performance shows that the PCMS-750 electrodes will be a potential candidate for energy storage.